Regeneration of Polylepis australis Bitt. in the mountains of central Argentina - Enrico, Lucas (2004)
Polylepis australis woodlands range from northern to central Argentina. They support a high number of endemisms (both plants and animals) and constitute the main cover type in watersheds contributing to retain soil and catch water. Natural regeneration of P. australis in the Córdoba mountains, Argentina, was studied in two communities dominated by P. australis: shrublands and woodlands. The main objectives of the study were: (1) to characterize shrublands and woodlands in terms of physical (physical and chemical soil properties) and biological (Polylepis’ growth form, fern and moss cover) characteristics; (2) to describe P. australis’ soil seed bank and compare seedling and sapling establishment between both communities. The presence of seedlings as well as saplings was quantified, and soil samples were taken so as to characterize the seed bank. Results showed significant differences in habitat conditions between shrublands and woodlands. Seedlings’ density was higher in the shrublands, while no differences appeared regarding the sapling numbers. A negative correlation was found between seedling numbers and total community cover as well as mosses and ferns cover. Seed density in the soil bank was higher in the woodlands, but overall seed viability was less than 5%. In the shrublands, the most critical stage of the species regeneration cycle was the transition from seedling to sapling, while in the woodlands the main “filter” occurred during seed germination. The low number of saplings observed in both units suggests a stagnation of P. australis regeneration, which could be translated into an unlikely expansion of the species throughout the Córdoba mountains.